Proceedings of the Climate Investment Funds, 2010 Partnership Forum, March 18-19, 2010, Manila, Philippines - World Bank (World Bank, Washington, DC, 2013)
The second Climate Investment Funds (CIF) partnership forum took place at the headquarters of the Asian Development Bank (ADB) in Manila, Philippines, on March 18-19, 2010. The objective of the 2010 partnership forum was to share lessons learned from the CIF design process and from early implementation of CIF-funded programs. The forum aimed to provide an open, transparent and constructive platform for dialogue on knowledge gained to date and to extract practical lessons learned by which to inform further implementation of the CIF. In particular, the partnership forum aimed to provide an opportunity to share early implementation lessons drawn from country-level activities of the Clean Technology Fund (CTF) and programs under the Strategic Climate Fund (SCF), particularly the Pilot Program on Climate Resilience (PPCR), and the first SCF program to advance to implementation stage.